Validity of Chronic Obstructive Pulmonary Disease Diagnoses in a Large Administrative Database. Issue 2 (2012) - Lacasse, Yves; Daigle, Jean-Marc; Martin, Sylvie; Maltais, François
Abstract : BACKGROUND: Administrative databases are often used for research purposes, with minimal attention devoted to the validity of the included diagnoses. AIMS: To determine whether the principal diagnoses of chronic obstructive pulmonary disease (COPD) made in hospitalized patients and recorded in a large administrative database are valid. METHODS: The medical charts of 1221 patients hospitalized in 40 acute care centres in Quebec and discharged between April 1, 2003 and March 31, 2004, with a principal discharge diagnosis of COPD ( International Classification of Diseases, Ninth Revision codes 491, 492 or 496) were reviewed. The diagnosis of COPD was independently adjudicated by two pulmonologists using clinical history (including smoking status) and spirometry. The primary outcome measure was the positive predictive value (PPV) of the database for the diagnosis of COPD (ie, the proportion of patients with an accurate diagnosis of COPD corroborated by clinical history and spirometry). RESULTS: The diagnosis of COPD was validated in 616 patients (PPV 50.4% [95% CI 47.7% to 53.3%]), with 372 patients (30.5%) classified as 'indeterminate'. Older age and female sex were associated with a lower probability of an accurate diagnosis of COPD. Hospitalization in a teaching institution was associated with a twofold increase in the probability of a correct diagnosis. CONCLUSIONS: The results support the routine ascertainment of the validity of diagnoses before using administrative databases in clinical and health services research.